The Impact of Religious Beliefs on Professional Ethics: A Case Study of a New Teacher - Barrett, Sarah Elizabeth (Canadian Journal of Education/Revue canadienne de l'éducation, 2015)
This case study of a math and science teacher in a private religious school looks at the impact of a teacher’s religious beliefs on her experience of engaging with ethical issues in her practice. A Freirean ethical framework is used to analyze her struggles with differences between her own personal religious convictions and those of the school in which she teaches, avoiding undue influence on her students’ developing beliefs, and the inherent violence of schooling. This case provides an example of ways in which discussions with teachers about professional ethics might be broadened beyond codes and regulations to the everyday embodied, social milieu in which they work.